Maternal inheritance in the efficiency of use of Azospirillum brasilense in maize - MICHELLI, Rafael Almeida [UNESP]; Da SILVA, Flávia Alves Marques [UNESP]; MORO, Gustavo Vitti [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
The maize crop demands high nitrogen input. However, Brazilian soils are generally deficient in this element. The use of associative bacteria, such as Azospirillum brasilense, can benefit agricultural systems that use low nitrogen levels. This study analyzes the occurrence of maternal inheritance in traits of maize genotypes for the efficiency of response to Azospirillum brasilense. For that, we used 132 treatments consisting of 66 crosses in complete diallel scheme with reciprocals. We evaluated two experiments in the same area and under the same conditions. We performed one experiment without nitrogen topdressing / with Azospirillum brasilense inoculation and another with nitrogen topdressing / without Azospirillum brasilense inoculation. These experiments took place in the second crop of 2017, in a randomized block design with two replicates. After obtaining the data, we estimated the efficiencies for the use of Azospirillum brasilense by adapting the Fischer model. From these data, we conducted analysis of variance, t test, and diallel analysis, thus estimating maternal inheritance. The evaluated traits showed no maternal inheritance, being governed by nuclear genes. Most genotypes were efficient for the use of A. brasilense, for all traits.
Keywords: Combining ability; Diallel analysis; Diazotrophic bacteria; Zea mays L